DYNAMICS OF CERTIFIED ENVIRONMENTAL MANAGEMENT SYSTEMS: ISO 14001 AND EMAS IN ROMANIA - RAȚIU, Patricia; MORTAN, Maria (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Confronted with more complex and numerous environmental issues many companies realized that environmental initiatives can be more effectively managed through an EMS which provide a systematic and coherent approach of their activities.  In the present paper we describe the two most recognized and widely applied systems for environmental management - EMAS (Eco-Management and Audit Scheme) and ISO 14001 certifications. Once viewed as an external cost, environmental responsibility is fast becoming a competitive advantage for companies and for the whole economy of a country. Our paper adds new perspective to the literature framework, by showing that even if the differences between ISO 14001 and EMAS still exist they are not competitors, moreover ISO 14001 requirements are integrated into EMAS scheme, become compatible to each other. To achieve the objective of this paper we make an analysis regarding the number of Romanian organizations that have a certified environmental management system, in compliance with the two main international references. The results show that in our countries the number of organizations with an EMS certified by ISO 14001 is much higher than the number of organizations registered under EMAS. This represents an opportunity, given that once with the adoption of EMAS II, ISO 14001 is a step stone towards EMAS certification and companies can integrate both standards in their management system, achieving more benefits on the European markets. Another opportunity to increase the number of EMAS registration are economic and financial incentives offered to small and medium sized companies.